Predicting Self-Esteem through Self-Advocacy and Assistive Technology Use among Adults with Physical Disabilities - Ramirez, Jacob; Kwon, Alicia (Psychological Research in Individuals with Exceptional Needs, 2024)
This study aims to examine the relationship between self-advocacy skills, assistive technology use, and self-esteem among adults with physical disabilities. A cross-sectional design was employed, with data collected from 244 adults with physical disabilities. Participants completed validated self-report measures assessing self-esteem, self-advocacy skills, and assistive technology use. Pearson correlation coefficients were calculated to explore the relationships between the variables. A linear regression analysis was conducted to determine the extent to which self-advocacy skills and assistive technology use predict self-esteem. All analyses were performed using SPSS version 27. The results indicated significant positive correlations between self-esteem and both self-advocacy skills (r = .62, p < .01) and assistive technology use (r = .58, p < .01). Self-advocacy skills and assistive technology use were found to be significant predictors of self-esteem, accounting for 49% of the variance (R² = .49, F(2, 241) = 115.63, p < .001). The regression analysis revealed that self-advocacy skills (B = 0.34, β = .42, p < .001) and assistive technology use (B = 0.28, β = .36, p < .001) both positively influence self-esteem. The study concludes that self-advocacy skills and assistive technology use are crucial determinants of self-esteem in adults with physical disabilities. These findings highlight the importance of providing support and training in self-advocacy and access to appropriate assistive technology to enhance psychological well-being and autonomy in this population. Future research should explore these relationships longitudinally and across diverse disability groups.